Developing Digital Comics Based on Local Wisdom for Fantasy Story Texts to Enhance Student Learning Outcomes - Mariani, Rika; Novita, Rita; Sari, Siti Mayang (Jurnal Komunikasi Pendidikan, 2024)
This research discusses the implementation materials Of comic-based teaching. This research aims to develop teaching materials for fantasy story texts based on local wisdom in the form of digital comics to improve the learning outcomes of fifth grade elementary school students. This research is research and development (R&D). In this research and development, researchers used the ADDIE method, Analysis, Design, Development, Implementation and Evaluation. The results of the development research show that the digital comic teaching materials based on local wisdom for grade V elementary school students produced are said to be very feasible. This is proven by the media expert validation results showing a very good category (96%) from the average validator. The material expert validation results show a very good category (96%) from the average validator. Linguist validation results show a very good category (98%) from the average validator. The results of the student response product trials showed the very good category (87.5%) and the results of the teacher response product trials showed the very good category (94%). In the evaluation of the test results, students obtained an average result of 89.71 with a percentage score of 90% with very good criteria with details of 28 students completing. This comic is a good idea for language learning based on students' interests and talents to improve their learning. The research results are proof that digital comic teaching materials based on local wisdom are very feasible and can be used as learning materials that can improve student learning outcomes.